2014
DOI: 10.1097/pts.0b013e31829e4f82
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hospital Systems Load and Patient Harm

Abstract: The results of this analysis are highly suggestive of a relationship between Hospital Systems Load and patient harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…53 It is impossible to determine the ideal number of employees in any given case without simultaneously looking at the quality of the work environment and workload, 54 and patients' need for care. However, it has been shown that workplace culture, especially the overarching factor of stress, correlates with the use of supplemental nursing staff and patients´ length of stay, 55 and also with the relationship between hospital system load and patient harm, 56…”
mentioning
confidence: 99%
“…53 It is impossible to determine the ideal number of employees in any given case without simultaneously looking at the quality of the work environment and workload, 54 and patients' need for care. However, it has been shown that workplace culture, especially the overarching factor of stress, correlates with the use of supplemental nursing staff and patients´ length of stay, 55 and also with the relationship between hospital system load and patient harm, 56…”
mentioning
confidence: 99%